2021
DOI: 10.1021/acs.jced.0c00962
|View full text |Cite
|
Sign up to set email alerts
|

Density and Electrical Conductivity for Aqueous Mixtures of Monoethylene Glycol and Sodium Chloride: Experimental Data and Data-Driven Modeling for Composition Determination

Abstract: Monoethylene glycol (MEG) is a gas hydrate inhibitor widely applied for natural gas flow assurance. A series of density and electrical conductivity measurements of water + MEG + NaCl mixtures are reported, allowing the supervision of the MEG regeneration unit. Density (509 data points) and electrical conductivity (212 data points) measurements were performed in wide ranges of temperature, T = 278.15–363.15 K, and concentration of solvents and NaCl up to almost saturation. The theory of solutions was applied fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The density calibration curves were determined at 298.15, 323.15, and 353.15 K. These calibration curves have been applied to the salt solubility determination at 293.15, 318.15, and 348.15 K. The 5 K difference between the calibration and solubility data curves was applied to avoid salt precipitation inside the density meter. Density experimental values used for the calibration curves were previously reported at 298.15 K by Moura-Neto et al and at 323.15 and 353.15 K by Moura-Neto et al …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The density calibration curves were determined at 298.15, 323.15, and 353.15 K. These calibration curves have been applied to the salt solubility determination at 293.15, 318.15, and 348.15 K. The 5 K difference between the calibration and solubility data curves was applied to avoid salt precipitation inside the density meter. Density experimental values used for the calibration curves were previously reported at 298.15 K by Moura-Neto et al and at 323.15 and 353.15 K by Moura-Neto et al …”
Section: Methodsmentioning
confidence: 99%
“…The density calibration curves were determined at 298.15, 323.15, and 353.15 K. These calibration curves have been applied to the salt solubility determination at 293.15, 318.15, and 348.15 K. The 5 K difference between the calibration and solubility data curves was applied to avoid salt precipitation inside the density meter. Density experimental values used for the calibration curves were previously reported at 298.15 K by Moura-Neto et al 30 and at 323.15 and 353.15 K by Moura-Neto et al 31 In order to demonstrate the validation of the experimental procedure used, values of the observed salt solubility have been compared to the data sets of Trimble, 12 Baldwin et al, 15 Massoudi et al, 13 and Zeng and Li; 18 As can be observed in Figure 2, experimental measurements present quantitative agreement with the literature. However, the work by Massoudi and co-authors 13 presented relatively high deviation in relation to the other authors.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, the approach proposed by Lorimer was applied for eight strong electrolytes in water–MEG mixtures. For the calculation of the density of pure water and MEG, and its mixtures, the equations reported by Moura‐Neto et al 20 were applied. Regarding dielectric constants for pure solvents, the equations reported by Åkerlöf 23 were used.…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…18,19 The regeneration process consists in removing salts and water by using mainly a vacuum flash separator and a distillation column. Thus, the accurate description of physicochemical properties 20 and phase behavior 21 for such ternary mixtures are of interest to the natural gas industry.…”
mentioning
confidence: 99%
“…Volumetric analysis is a crucial method of elucidating the physicochemical phenomena of solutes in solution. Moreover, the viscosity and refractive index of the mixed solution are two other important parameters that can provide valuable information for a better understanding of intermolecular interactions. It is well known that most biochemical processes occur in aqueous media. Therefore, research on the volumetric properties, viscometric properties, and refractive indices of drugs in aqueous media is helpful for deepening the understanding of drug molecular interactions, which contributes significantly to advancements in the fields of pharmacy and pharmaceutical chemistry. However, the drug–solvent interactions that can elucidate the solvation behavior of drugs in vivo are difficult to investigate directly because of the presence of various cosolutes, such as carbohydrates, amino acids, salts, proteins, and so forth in biosystems.…”
Section: Introductionmentioning
confidence: 99%